Fatal aspergillosis and evidence of unrelated hearing loss in a harbor porpoise (Phocoena phocoena) from the German Baltic Sea - Rohner, Simon; Morell, Maria; Wohlsein, Peter; Stürznickel, Julian; Reiter, Eva B.; Jahnke, Annika; Prenger-Berninghoff, Ellen; Ewers, Christa; Walther, Grit; Striewe, Lotte C.; Failla, Antonio Virgilio; Siebert, Ursula (Frontiers in Marine Science, 2022)
Detailed post-mortem investigations including the auditory pathway are needed to advance our understanding of how underwater noise and other stressors affect hearing in cetaceans. A 12-year-old female porpoise (Phocoena phocoena) stranded alive in June 2021 at the German Baltic Sea coast and died some hours later. The most significant pathological findings were lesions caused by a severe aspergillosis that spread from the lung and pulmonary lymph node to the cerebellum. Based on molecular sequencing, the fungus was identified as Aspergillus fumigatus. Severe pyogranulomatous and necrotizing inflammation was diagnosed in the lung and the associated lymph node. In the left part of the cerebellum, focal, severe purulent and necrotizing meningoencephalitis with intralesional fungal structures was confirmed histologically. In addition, multifocal, severe, chronic, granulomatous, and eosinophilic gastritis with intralesional parasite structures was found in the stomach. Parallel stripes (linear skin markings) were detected along the caudal part of both body sides, which have not been previously described for harbor porpoises. Inner ear analysis revealed evidence of focal loss of outer hair cells in several regions from 120 to 580 µm from the apex of the right cochlea using immunofluorescence. The evidence of low-frequency hearing impairment was compatible with noise-induced hearing loss. This is the first case of concurrent presumptive noise-induced hearing loss and unrelated aspergillosis in a free-ranging harbor porpoise.